The Comparison of Jejuno-Ileal Bypass and Transit Bipartition in Patients with Type 2 Diabetes Mellitus: Preliminary Report - Taskin, Halit Eren; Rzayev, Elshad; Kirkil, Cuneyt; Belen, Nurhan Haluk; Karahan, Veysel; Zengin, Abdullah Kagan; Taskin, Mustafa (Springer, 2018)
[Abstract Not Available]
8th Congress of the European-Chapter of the International-Federation-for-the-Surgery-of-Obesity-and-Metabolic-Disorders (IFSO-EC) -- MAY 17-19, 2018 -- Athens, GREECE